2023
DOI: 10.3390/ijerph20042891
|View full text |Cite
|
Sign up to set email alerts
|

Association between Problematic Use of Smartphones and Mental Health in the Middle East and North Africa (MENA) Region: A Systematic Review

Abstract: Smartphones have become essential components of daily life, and research into the harmful effects of problematic smartphone use (PSU) on mental health is expanding in the Middle East and North Africa (MENA) region. This issue has yet to be synthesized and critically evaluated. To find quantitative observational studies on the relationship between PSU and mental health in the MENA region, we developed a search equation and adapted it for four databases. The Preferred Reporting Items for Systematic Review and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The results in Table 2 also depicted that anxiety was quite higher in females than in males within the UAE. This finding is not surprising at all as countless studies (including countries within the MENA region, like the UAE, KSA, and Kuwait) have illustrated this finding repeatedly [ 41 45 ]. Many researchers have a plethora of explanations as to why there is a gender difference between anxiety levels.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results in Table 2 also depicted that anxiety was quite higher in females than in males within the UAE. This finding is not surprising at all as countless studies (including countries within the MENA region, like the UAE, KSA, and Kuwait) have illustrated this finding repeatedly [ 41 45 ]. Many researchers have a plethora of explanations as to why there is a gender difference between anxiety levels.…”
Section: Discussionmentioning
confidence: 86%
“…As an individual uses their smartphone more in an uncontrolled manner, a greater capacity for depression becomes feasible. Analogous to this is a study done across the MENA region where problematic smartphone usage was heavily associated with both anxiety and depression, as well as stress [ 41 ]. A study conducted amongst university students in Lebanon found that there was a statistically significant correlation between an individual with depression and anxiety, and smartphone usage, where it was deduced that its addiction could be due to a need for a coping mechanism or is used as an approach to managing one’s mood [ 76 ].…”
Section: Discussionmentioning
confidence: 97%